Application of ABB in environmental management accounting: Incorporating MFCA into the budget process - Qu, Longyu; Wang, Zhan; Sun, Chang; Yin, Linsen (Frontiers in Environmental Science, 2022)
In this study, we introduce the Material Flow Cost Accounting (MFCA) method into the budgeting process of manufacturing firms, and thus construct an MFCA-ABB (Activity-Based Budget) model. This model is applied to the target company in order to forecast and plan for its resource consumption, positive product output, and negative product emissions. Based on the forecasts of involved material flows, inefficiencies in the company's liquor production process are identified; scenario analysis is then conducted to determine the optimal process and the technology adopted. The proposed MFCA-ABB model turns a pure operating budget into an environmental-economic budget, thus achieving both environmental and economic benefits for the company. Besides, this study makes an attempt to apply ABB in environmental management accounting, which suggests the possibility of applying the conventional management accounting tools, after modified, to the environmental-economic management of manufacturing firms in the future.